(untitled) (Sains Humanika, 2013)
This paper presents a case study that highlights online mentoring among pre-service teachers and in-service teachers from three local public tertiary institutions. Specifically, it investigates the roles of mentees during virtual mentoring sessions. Four groups of pre-service teachers from three local tertiary institutions mentored by four in-service teachers from Johor Bahru participated in the study. Each group was assigned an online newsletter and required to carry out writing of the online newsletter task by discussing through Nicenet, an online forum, when carrying out the task. The data obtained from the online postings on Nicenet was analyzed using Ambrosetti and Dekkers’s (2010) roles of mentees. Findings implied that the e-mentees acted as supporters, active participants, collaborators, leaders, and role models. The findings also revealed three salient themes which are: i) collaboration as an inevitable practice, ii) the need for mentees to be actively involved in mentoring practice and iii) the lack of experience and self-esteem among mentees.